Pemberdayaan Masyarakat Miskin Kota - Emiliana Martuti Lawalu; Adrianus Ketmoen; Benurtiana Vevin (Ekopem: Jurnal Ekonomi Pembangunan, 2022)
The objectives of this study are 1) To determine the implementation of the program, family hope (PKH) in empowerment in Naimata village, Kupang City. 2. To find out the impact of the family hope program for the urban poor in Naimata village, Kupang City. The method used is qualitative descriptive analysis. The data used in this study were primary data and secondary data with the research subjects, namely the recipients of PKH in Naimata village, Kupang City, which amounted to 50 informants. The results showed that 1. the implementation of PKH in Naimata in terms of Planning, Organizing and implementation has been running quite optimally, this can be seen by the increasing number of PKH recipients in 2020 Making the community experience changes, especially in mindset and behavior as well as continuity towards improving the lives of Beneficiary Families. 2. This program has proven that the large number of recipients of the Family Hope Program in 2020 can improve education and health aspects, such as increasing access to health services at the puskesmas, increasing the education level of school children, providing adequate assistance and establishing coordination between relevant agencies in the success of the program. Hope Family Program.